Application of methods of recalculation of gasdynamic characteristics of multi-staged and multisection turbocompressors on other conditions of work in various technological installations - A. D. Vanyashov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis of influence of methods of count of gasdynamic characteristics of multistage and multisection centrifugal compressors on other working conditions (productivity, pressure, temperature, composition of gas on an input in the compressor, rotating speed of a rotor), on the form of the gasdynamic characteristic, the range of operating modes is made. Real production objects on blueprint stages, tests, maintenance are considered. In the course of approbation of calculation methods of count project data are used as the experimental. Recommendations are given and scopes of an advanced method of stage-by-stage count of gasdynamic characteristics of the compressor taking into account a mismatch in operation of steps are defined